MK-886 enhances tumour necrosis factor-alpha-induced differentiation and apoptosis - Stika, Jirí; Vondrácek, Jan; Hofmanová, Jirina; Simek, Vladimír; Kozubík, Alois (Cancer letters, 2006)
We investigated the role of the 5-lipoxygenase (5-LOX) pathway of arachidonic acid metabolism in tumour necrosis factor-alpha (TNF-alpha)-induced differentiation of human leukemic HL-60 cells using MK-886, an inhibitor of 5-LOX activating protein. MK-886 augmented cell cycle arrest and differentiation induced by TNF-alpha; however, both effects were probably 5-LOX-independent, because a general LOX inhibitor, NDGA, had no effect. Apoptosis was significantly elevated after combined TNF-alpha and MK-886 treatment, which could be partially associated with changes of Mcl-1 protein expression. NF-kappaB signalling or activation of JNKs were not modulated by MK-886. Thus, in addition to apoptosis, MK-886 can enhance TNF-alpha-induced differentiation.
Keywords: Indoles; apoptóza; HL-60 buňky; indoly; Arachidonate 5-Lipoxygenase; Cell Line, Tumor; inhibitory lipoxygenas; Tumor Necrosis Factor-alpha; Apoptosis; Cell Cycle; Time Factors; časové faktory; Lipoxygenase Inhibitors; buněčná diferenciace; lidé; signální transdukce; HL-60 Cells; Signal Transduction; buněčný cyklus; TNF-alfa; arachidonát-5-lipoxygenasa; Cell Differentiation; Cell Survival; viabilita buněk; nádorové buněčné linie; Humans